Two new secondary metabolites from a mangrove-derived fungus Cladosporium sp. JJM22. Issue 1 (2nd January 2019) - Wu, Jia-Ting; Zheng, Cai-Juan; Zhang, Bin; Zhou, Xue-Ming; Zhou, Qi; Chen, Guang-Ying; Zeng, Zhuo-Er; Xie, Jin-Long; Han, Chang-Ri; Lyu, Ji-Xing
Abstract: Two new compounds (1 and2 ), together with six known compounds (3–8 ), were obtained from the Cladosporium sp. JJM22, an endophytic fungus isolated from the stem bark of the mangrove plant Ceriops tagal collected in South China Sea. Their structures were elucidated on the basis of detailed spectroscopic analysis. The absolute configurations of1 and2 were confirmed by the comparison of optical rotation and the CD data with those of known compounds. The inhibitory activities of the isolated compounds against six terrestrial pathogenic bacteria and human cervical carcinoma Hela cell line were evaluated. Compound3 exhibited a broad spectrum of antibacterial activities. Abstract :